2020
DOI: 10.1002/ece3.7064
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and nutritional environments during development exert different effects on adult reproductive success in Drosophila melanogaster

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 94 publications
1
15
1
1
Order By: Relevance
“…A recent study (Duxbury & Chapman, 2020), which aimed to test between the silverspoon and environmental matching hypotheses, manipulated developmental and adult nutrition, and found that female reproductive senescence was affected by an interaction between developmental and adult diets. However, another study that manipulated both adult and developmental temperatures in Drosophila found results similar to ours (Min et al, 2020). Specifically, they found that adult temperature had a greater effect on age-dependent survival than developmental temperature, and that hot adult temperatures were deleterious for adult survival senescence.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A recent study (Duxbury & Chapman, 2020), which aimed to test between the silverspoon and environmental matching hypotheses, manipulated developmental and adult nutrition, and found that female reproductive senescence was affected by an interaction between developmental and adult diets. However, another study that manipulated both adult and developmental temperatures in Drosophila found results similar to ours (Min et al, 2020). Specifically, they found that adult temperature had a greater effect on age-dependent survival than developmental temperature, and that hot adult temperatures were deleterious for adult survival senescence.…”
Section: Discussionsupporting
confidence: 79%
“…Additional complexity to the tangled interactions between early and late life conditions arises from the fact that responses to environmental stimuli can be trait-and sex-dependent (e.g. Duxbury & Chapman, 2020;Helle et al, 2012;Krause et al, 2017;Min et al, 2020;Pigeon et al, 2019;Santos et al, 2021;Scharf, Braf et al, 2015;Stillwell & Fox, 2005). For example, in cichlids reproductive rate is determined only by nutrition during development, while adult growth rate is determined only by nutrition in the adult stage, and clutch size is determined by both developmental and adult life nutrition (Taborsky, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…One popular empirical approach for implementing the mismatched environment 8 test for PARs relies on estimating a regression with interaction effects between developmental and adult environmental quality 9 [e.g. 14, 27, 26, 32, 11, 63, 33, 52, 42], i.e., where u is a regression error term. We will hereafter refer to this equation as the interaction regression.…”
Section: Mathematical Definitions and Predictionsmentioning
confidence: 99%
“…(2016) MgO NP'lerinin morfin yoksunluğunun neden olduğu anksiyete üzerindeki etkilerinin erkek fareler üzerinde araştırıldığı çalışmada akut ve kronik MgO NP enjeksiyonlarının morfin yoksunluğu çeken erkek farelerde kaygı benzeri davranışları önemli ölçüde azalttığını tespit etmişlerdir. D. melonagaster için besin ortamı ve ortam sıcaklığının hayatta kalma ve üreme kabiliyeti üzerinde etkileri olduğu bilinmektedir (Min et al 2021). Pompa vd.…”
Section: Negatif Jeotaksis Deneyiunclassified